2009
DOI: 10.1007/s12562-009-0085-1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of a self-assembled fibrillar gel prepared from red stingray collagen

Abstract: A translucent collagen gel was formed from a transparent acidic solution of red stingray collagen by adjusting to physiological ionic strength and pH in phosphate buffer and then incubating at 25-37°C. During fibril formation from red stingray collagen, the turbidity increased when the NaCl concentration was increased at constant pH and the rate of fibril formation was accelerated by higher pH or lower NaCl concentration. The T m of red stingray collagen fibrillar gel was estimated as 44.3 ± 3.5°C, which was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…This inference is true for both SBC and SC. There have been a few studies on the fibrillogenesis of type I collagen and the morphology of the fibrils formed in vitro in fish collagens, such as those from salmon skin [26], shark skin [31], red stingray skin [32], Bester sturgeon skin, and swim bladder [27]. However, these studies focused on the influence of monovalent ions only, such as Na + and Cl -.…”
Section: Discussionmentioning
confidence: 99%
“…This inference is true for both SBC and SC. There have been a few studies on the fibrillogenesis of type I collagen and the morphology of the fibrils formed in vitro in fish collagens, such as those from salmon skin [26], shark skin [31], red stingray skin [32], Bester sturgeon skin, and swim bladder [27]. However, these studies focused on the influence of monovalent ions only, such as Na + and Cl -.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of fibril formation was monitored by measuring the turbidity changes as observed by the increase in absorbance at 310 nm using a UV spectrophotometer (UV‐2000, Unico, Shanghai, China). The degree of fibril formation was determined by the method of Bae et al Briefly, a collagen fibrillar gel was prepared in a centrifugation tube by the procedure described above. After 24 h of incubation, the gel was centrifuged at 10 000 × g for 10 min at 4 °C to precipitate the collagen fibrils, which were collected for analysis of fibril morphology.…”
Section: Methodsmentioning
confidence: 99%
“…The degree of rohu skin collagen fibril formation significantly (p≤0.05) higher (up to 78% at 1500 mM NaCl concentration) as compared with catla skin collagen (36%). Bae et al (2009) andZhang et al (2014) have reported an increase in the degree of fibril formation with increasing NaCl concentration.…”
Section: Degree Of Collagen Fibril Formationmentioning
confidence: 99%